Analisis Hubungan Jumlah Aparatur Sipil Negara dengan Cakupan Layanan Dasar Pendidikan dan Kesehatan di Kabupaten Bangka Tahun 2020-2024 - Delliya, Delliya; Sofyan, Agus; Hidayat, Wahyu (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to analyze the relationship between the number of civil servants (ASN) and the coverage of basic education and health services in Kabupaten Bangka during the 2020–2024 period. The study employs a quantitative approach using a library research method, supported by descriptive analysis, Pearson correlation tests, and simple linear regression. The data used are secondary data consisting of the number of ASN teachers and health personnel, service ratios, and indicators of basic education and health service coverage. The correlation test results show that the relationship between the number of ASN teachers and education service coverage has a correlation coefficient of r = 0.213 with a significance value of p = 0.642 (p > 0.05), indicating a weak and statistically insignificant relationship. Meanwhile, the correlation between the number of ASN health personnel and health service coverage yields r = 0.178 with a significance level of p = 0.701 (p > 0.05), which also reflects a very weak and statistically insignificant relationship. The regression analysis further supports these findings, as the coefficient of determination for the education sector is only R² = 0.045, and for the health sector R² = 0.032, suggesting that the number of ASN explains only a very small proportion of the variance in service coverage. These findings indicate that ASN policies focused solely on increasing personnel quantity are not necessarily effective in improving public service quality unless accompanied by optimal management, equitable distribution, competency development, and effective utilization of ASN. Therefore, policy evaluation at the regional level should emphasize effectiveness, performance, and strategic allocation of ASN rather than merely increasing the number of personnel.